The impact of deformation in the zone of welded joints on the force action of the rolling stock on the track - V. S. Kossov; O. G. Krasnov; M. G. Akashev (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
The causes of deformation in the zone of welded joints are considered. Authors experimentally studied changes in hardness on the rolling surface of the rail in the longitudinal and transverse profiles within the thermally affected zone of the welded joint. It is established that the hardness of the rolling surface of the rail in the longitudinal direction in the thermally affected zone of the joint is uneven and is determined by the structures arising from the effects of the thermal cycles of welding and the quality of the local heat treatment. In this case, two "low spots" are clearly traced with a decrease in hardness to 290...300 HB and with a higher hardness up to 350 HB right in the welded joint. Experimentally investigated the change in the depth of the welded joint from the implemented tonnage. At the same time with strain gauge method, using the force method developed by N. N. Kudryavtsev, continuous changes in vertical forces when the wheels move along the welded joint zone were recorded. Average values of vertical forces from loaded cars were established. Experimental distributions of vertical forces were approximated by theoretical laws according to the Kolmogorov — Smirnov matching criterion. Recommendations are given on minimizing the harmful impact of rolling stock on the track in areas of lowering welded joints.The following conclusions were made.1.            Geometry of the joint irregularity is in the form of a W-shaped deformation with an influx of metal on the receiving rail and lowering on the directing rail. The width of the upper part of the deformation varies between 160...200 mm along the axis of the rail.2.            Deformation zone of the welded joint is a source of increased dynamic impact from the wheels of the rolling stock on the elements of the upper track structure. According to the results of experimental studies it was found that the greatest increase in dynamic effects was observed from locomotive wheels up to 45..               . 70 kN, maximum values reached 180...210 kN, from the wheels of loaded freight cars the values of vertical forces increased by 35..     .45 kN, maximum values reached 145...170 kN, from the wheels of empty cars increase dynamic impacts amounted to 14...16 kN, maximum values reached 32...36 kN.